Enhancing temozolomide in vivo stability and efficacy through hybrid nanoconjugate approach for improved glioblastoma multiforme treatment - Prabhjeet Singh; Deepak Kumar Sahel; Reena Jatyan; Kiran Bajaj; Anupama Mittal; Deepak Chitkara (Asian Journal of Pharmaceutical Sciences, 2025)
Temozolomide (TMZ) is considered as a standard-of-care DNA alkylating agent for treating glioblastoma multiforme. Despite being a highly potent molecule, TMZ poses several limitations, including short half-life, rapid metabolism, low brain bioavailability and dose-dependent toxicities. Attempts have been made to improve the delivery of TMZ that mainly exhibited nominal therapeutic outcomes. In the current study, we have conjugated TMZ to mPEG-b-P(CB-{g-COOH}) copolymer to obtain mPEG-b-P(CB-{g-COOH; g-TMZn}) that demonstrated improvement in stability and efficacy. Further, a hybrid TMZ nanoconjugate formulation was developed using mPEG-b-P(CB-{g-COOH; g-TMZ40}) and mPEG-polylactic acid (mPEG-PLA) showed an average size of 105.7 nm with narrow PDI of <0.2 and TMZ loading of 21.6%. Stability was assessed under physiological conditions wherein TMZ was found to be stable with a half-life of ∼194 h compared to 1.8 h for free TMZ. The Hybrid TMZ nanoconjugates showed improved intracellular uptake and reduced IC50 values in C6 and U87MG glioma cells. Furthermore, they exhibited better in vivo therapeutic outcome, i.e., reduced brain weight, hemispherical width ratio and improved survival rate in C6-cell induced orthotropic glioma model in Sprague Dawley rats compared to the free TMZ-treated and positive control animals. Histopathological evaluation also revealed reduced cell infiltration in the lungs and reduced toxicity in major organs. Overall, the hybrid nanoconjugates of TMZ significantly improved its stability and efficacy in the GBM model, thereby opening newer avenues for treatment.